How to be an elephant : growing up in the African wild - Roy, Katherine (David Macaulay Studio, Roaring Brook Press, 2017)
This nonfiction picture book follows an elephant's growth from a newborn calf to a full-grown adult in one of the most socially and structurally complex family groups on earth.--